Intraoperative Anti-Parasitic Treatment of The Residual Cavity After Echinococcectomy from The Liver - Kurbaniyazov Zafar Babazhanovich; Rakhmanov Kosim Erdanovich; Salohiddinov Jurabek Sayidakhmatovich; Makhramkulov Zafar Mamerkulovich (Periodica Journal, 2022)
The article presents modern views on the etiology, pathogenesis and treatment of liver echinococcosis. The toxic effect on the liver of drugs of the Albendazole group is considered. The results of the use of the drug Albendazole as a local germicidal agent according to the method developed at the Department of Surgical Diseases №1, Samarkand State Medical Institute are considered
Keywords: Echinococcosis of the liver; chemotherapy of echinococcosis; Albendazole; Spongostan sponge